Death with laughter: the subject of the unconscious in Martin McDonagh's Hangmen. - Kolahjooei, Farzad (Studies in Theatre & Performance, 2026)
This paper provides a discussion of Lacanian subjectivity and desire in Martin McDonagh's Hangmen. While it might seem an attempt to argue against capital punishment, as many critics have indicated, the play has unconscious undertones that reveal certain facts about the subject's deepest motives. McDonagh's portrayal of depthless characters, who are limited in knowledge and blind to anything other than their unchecked, wild desires, underscores the void at the core of subjectivity. I will argue that the circular structure of Hangmen, which starts and ends with death, implicates the audience in actions that highlight an existentially absurd, cynical view of human desire. I will further discuss how Lacan's concept of the gaze helps us understand McDonagh's reconsideration of the relationship between the audience and the play.